IMPLIKASI PERCERAIAN (Kajian Tentang Akibat Lain yang Ditimbulkan Oleh Sebuah Peristiwa Hukum) - Muhammad Farid (Al-Bayyinah, 2017)
Marriage is an another space in episode of human lifeway. Actually, it gives satisfied in brotherhood and thefirst in relatives. But sometimes when the time goes on, themarriage commitment changes extremely; it claimsdivorce. Indeed, if we try to contemplate, their is much wehave done to develop the life our marriage, namely:introduction each other (side of relatives of husband andwife), wedding party, life in happy an unhappy; and all ofthem has taken our budget, energy and thought.Normality, if syariat Islam is followed seriously, of courseno anymore marriage till divorce, there is a case to bethought: children. They will be loosed parent, theresource of their happiness. So think ones more to divorce